The Use of Flaps and Grafts in the Treatment of Urethral Stricture Disease - Eric S. Wisenbaugh; Joel Gelman (Advances in Urology)
The use of various grafts and flaps plays a critical role in the successful surgical management of urethral stricture disease. A thorough comprehension of relevant anatomy and principles of tissue transfer techniques are essential to understanding the appropriate use of grafts or flaps to optimize outcomes. We briefly review these principles and discuss which technique may be best suited for a given anterior urethral stricture, depending on the location and length of the stricture, the presence or absence of an intact corpus spongiosum, and the availability of adequate and healthy penile skin.